مستوى اكتساب المفردات اللغوية لدى طلبة المركز التمهيدي بجامعة العلوم الإسلامية الماليزية - Mohamad Hazwan Abdul Rahman
The aim of this study is to see the level of proficiency of Arabic vocabulary among students from Tamhidi Centre, Islamic Science University of Malaysia (USIM). Researcher used quantitative studies and survey forms were distributed to 100 male and female students randomly from 5 different programmes, for instance: Tamhidi of Medic, Tamhidi of Dentistry, Tamhidi of Science and Technology, Tamhidi of Shariah and Law, and Tamhidi of Accounting and Muamalat. Respondents are required to translate the meaning of Arabic words. The data were analyzed using the SPSS to look at the ratio of frequencies, percentages, means, and analysis of the relationships between variables. From this study, the researcher found that the level of Arabic language proficiency among Tamhidi students was moderate. Therefore, the researcher also explains the factors that lead to the weakness of vocabulary from the respondents' perspective. At the end of the study, several proposed improvements were shared to benefit the university and the person that responsible for this area.